Numerical Calculations for Hovering Performance of a Rotor in Partial Ground Effect - ITOGA, Noriaki; IBOSHI, Naohiro (Journal of Japan Society of Fluid Mechanics, 2004)
Modern day helicopters are frequently required to operate in various flight situations. It is a case in point that a helicopter hovers closely and partially above a heliport which is on top of a high-rise building and the helicopter rotor is subject to Partial Ground Effect. In such flight situations, it is important to grasp effects of the complex ground geometry on rotor aerodynamic performance quantitatively. In this paper, the horizontal distance from rotor hub center to ground edge and the rotor height are adopted as parameters of Partial Ground Effect and based on the vortex method, we predict numerically the effect of such parameters on collective pitch angle, induced torque and coning angle of a hovering rotor in Partial Ground Effect. After discussing validity of the numerical method by comparing numerical results with experimental data, it is also clarified by showing flowfields around the rotor that due to the rotor wake contraction, there is a specific horizontal distance range where the rotor performance are not consistent with the geometric flight environment between rotor plane and boundary plane.